Von Willebrand factor fibers promote cancer-associated platelet aggregation in malignant melanoma of mice and humans - Bauer, Alexander; Desch, Anna; Wagner, Andreas H.; Hecker, Markus; Utikal, Jochen; Gorzelanny, Christian; Umansky, Viktor (Blood, 2015)
Tumor-mediated procoagulatory activity leads to venous thromboembolism and supports metastasis in cancer patients. A prerequisite for metastasis formation is the interaction of cancer cells with endothelial cells (ECs) followed by their extravasation. Although it is known that activation of ECs and the release of the procoagulatory protein von Willebrand factor (VWF) is essential for malignancy, the underlying mechanisms remain poorly understood. We hypothesized that VWF fibers in tumor vessels promote tumor-associated thromboembolism and metastasis. Using in vitro settings, mouse models, and human tumor samples, we showed that melanoma cells activate ECs followed by the luminal release of VWF fibers and platelet aggregation in tumor microvessels. Analysis of human blood samples and tumor tissue revealed that a promoted VWF release combined with a local inhibition of proteolytic activity and protein expression of ADAMTS13 (a disintegrin-like and metalloproteinase with thrombospondin type I repeats 13) accounts for this procoagulatory milieu. Blocking endothelial cell activation by the low-molecular-weight heparin tinzaparin was accompanied by a lack of VWF networks and inhibited tumor progression in a transgenic mouse model. Our findings implicate a mechanism wherein tumor-derived vascular endothelial growth factor-A (VEGF-A) promotes tumor progression and angiogenesis. Thus, targeting EC activation envisions new therapeutic strategies attenuating tumor-related angiogenesis and coagulation.